The brain encyclopedia - Turkington, Carol (New York : Checkmark Books, 1996)
A-to-Z guide to the workings of the brain, providing information on its structure and development, brain mapping, injuries, diseases, and disorders, and answering questions about its functions, with a listing of organizations that deal with brain diseases.
Includes bibliographical references (p. 276-286) and index.
Booklist.
Library Journal.
Wilson's Public Library.
Young Adult
Keywords: Brain -- Encyclopedias; Neurology -- Encyclopedias; Brain -- Encyclopedias; Nervous system -- Encyclopedias